ANALYSIS PLANNING AND DESIGN STRUCTURE OF BUILDING FLATS RENT FOR FACTORY WORKERS IN INDUSTRIAL AREA CIREBON REGENCY - Taufik Nurrohman; Fathur Rohman (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2019)
ABSTRACTThe industrial area in Cirebon Regency which has absorbed a number of industrial workers need to be supported by the infrastructure that facilitates the existence of industrial workers from inside and outside of Cirebon Regency, namely is residence that becomes one of the primary needs / basic human and they should find a place to live that suits the needs and financial capabilities. According to the Constitution 1945, Law No. 4 1992 Housing and Settlement and the Law No. 39 of 1999 on Human Rights, the house is the people's basic rights and guaranteed by law and supported by the Presidential Decree 22/2006 issued a national program